2015
DOI: 10.6061/clinics/2015(02)01
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the total atrial conduction time to subclinical atherosclerosis, inflammation and echocardiographic parameters in patients with type 2 diabetes mellitus

Abstract: OBJECTIVES:The aim of our study was to evaluate the total atrial conduction time and its relationship to subclinical atherosclerosis, inflammation and echocardiographic parameters in patients with type 2 diabetes mellitus.METHODS:A total of 132 patients with type 2 diabetes mellitus (mean age 54.5±9.6 years; 57.6% male) and 80 age- and gender-matched controls were evaluated. The total atrial conduction time was measured by tissue-Doppler imaging and the carotid intima-media thickness was measured by B-mode ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Roshanalli et al showed that the atrial electromechanical interval is a predictor of AF developing after coronary artery bypass grafting, and preoperative administration of amiodarone to patients with a longer atrial electromechanical interval reduces the incidence of postoperative AF [19]. Previous studies have shown that atrial EMD is prolonged in many clinical disorders such as mitral stenosis, diabetes mellitus, hypertension, psoriasis, and inflammatory bowel disease [20][21][22][23][24]. Also, the incidence of AF in these diseases has increased significantly compared to the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…Roshanalli et al showed that the atrial electromechanical interval is a predictor of AF developing after coronary artery bypass grafting, and preoperative administration of amiodarone to patients with a longer atrial electromechanical interval reduces the incidence of postoperative AF [19]. Previous studies have shown that atrial EMD is prolonged in many clinical disorders such as mitral stenosis, diabetes mellitus, hypertension, psoriasis, and inflammatory bowel disease [20][21][22][23][24]. Also, the incidence of AF in these diseases has increased significantly compared to the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…Roshanalli et al showed that the atrial electromechanical interval is a predictor of AF developing after coronary artery bypass grafting, and preoperative administration of amiodarone to patients with a longer atrial electromechanical interval reduces the incidence of postoperative AF (19). In addition, it has been shown in previous studies that atrial EMD is prolonged in many clinical disorders such as mitral stenosis, diabetes mellitus, hypertension, psoriasis, and Inflammatory Bowel Disease (20)(21)(22)(23)(24). In addition, the incidence of AF in these diseases has increased significantly compared to the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…Although they were asymptomatic and the vast majority was free of clinical congestion, some were treated with loop diuretic and, had they been breathless, would have fulfilled our criteria for a diagnosis of HFpEF, a difficult diagnosis to make (22)(23)(24). Moreover, many of the controls suffered from hypertension and/or type II diabetes, two common comorbidities that might increase the risk of heart failure (22), atrial fibrillation and prolong the P-A´TDI interval (25): is possible that P-A´TDI interval might be shorter in individuals who are entirely free of cardiovascular risk factors. In those without HF, those with DM had a longer lateral, but not septal, P-A´TDI interval than those without DM (septal P-A´TDI: DM -99 (21) ms, no DM: 90 (18) ms, p=0.078; lateral P-A´TDI: DM -121 (22) ms, no DM: 109 (22) ms, p=0.026).…”
Section: Study Limitationsmentioning
confidence: 99%